Vertical and horizontal corneal epithelial thickness profiles determined by ultrahigh resolution optical coherence tomography - Du, Chixin; Wang, Jianhua; Cui, Lele; Shen, Meixiao; Yuan, Yimin (Cornea, 2012)
To measure vertical and horizontal thickness profiles of the central and peripheral corneal epithelium and determine if daytime changes occur. Forty eyes of 20 normal subjects were imaged by ultrahigh resolution spectral domain optical coherence tomography to profile the corneal epithelial thickness from the edge of Bowman layer to the central cornea across the vertical and horizontal meridians. Measurements were made at 10:00 AM and again at 6 and 8 hours later. The baseline vertical meridional epithelial thickness was thinnest, 42.9 ± 4.1 μm, at the edge of Bowman layer in the superior region. It increased in thickness (P < 0.01), toward the central cornea. The central epithelium averaged 52.5 ± 2.4 μm, becoming thickest, 55.2 ± 2.5 μm, in the inferior pericentral region. It thinned toward the inferior periphery, reaching 51.3 ± 5.1 μm at the edge of Bowman layer (P < 0.01). Along the horizontal meridian, the epithelium was thickest at the nasal side, 58.6 ± 5.1 μm, and temporal side, 59.3 ± 6.6 μm, near the edges of Bowman layer. It thinned toward the central cornea. There were no significant changes in the epithelial thickness at any location over 8 hours. Epithelial thickness varied over the horizontal and vertical meridians and appeared stable during the daytime.